An analytical study of seismoelectric signals produced by 1-D mesoscopic heterogeneities - Monachesi, Leonardo B. (2015)
Fil: Monachesi, Leonardo B. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.